Glycemic Index Trends and Clinical Implications: Where Are We Going? (2018)
Glycemic index (GI) is currently considered as an alternative system that classifies food according to the carbohydrate quality (CHO), measuring its absorption speed; meanwhile, glycemic load GL is a more recent term that relates the quality and quantity of the CHO per gram of the usual consumption portion. Glycemic index and glycemic load reduce the post-prandial glycemic impact without the total restriction of CHO in the diet. Initially, GI was used only in patients with diabetes, currently it is also considered as a risk indicator in other pathologies. However, there is great controversy due to an inaccurate interpretation of the knowledge about the methodology used for its determination. The aim of this review is to elucidate this current debate and to expand the relationship between the GI and the risk of diabetes and other chronic diseases; thus, highlighting new prospects for its applicability in the dietary intervention for diabetic athletes and in the production of functional food designed for patients with diabetes. There is strong evidence that this indicator has become an innovative system for various multidisciplinary health programs.